Weekend effect on in-hospital outcomes of transcatheter aortic valve replacement: insights from a propensity-matched national analysis - Guangzhi Cong; Bo Shi; Xueping Ma; Congyan Ye; Rui Yan; Shizhe Fu; Kairu Wang; Haowei Li; Ru Yan; Shaobin Jia; Israel Gitangaza; Abdul Rehman (BMC Cardiovascular Disorders)
Abstract Background The “weekend effect” on hospital admissions has been extensively studied, showing increased risks for patients admitted on weekends than those admitted on weekdays. We aimed to assess the “weekend effect” on in-hospital outcomes in patients undergoing transcatheter aortic valve replacement (TAVR). Methods A nationwide cohort study was conducted using the National Inpatient Sample Database. We identified 82,094 eligible patients aged ≥ 18 years admitted for TAVR between 2013 and 2021. Patients were grouped into weekend or weekday cohorts based on day of admission. Propensity score matching (PSM) and multivariate regression models were employed to evaluate outcomes. After PSM, 2,688 weekend admissions and 13,440 weekday admissions were included in the analyses. Results Multivariable regression, adjusted for propensity score, revealed that weekend admission was associated with 45% higher odds of in-hospital mortality (adjusted odds ratio: 1.45; 95% confidence interval: 1.13–1.85). Significant heterogeneity in mortality was observed based on admission urgency, with a 3.27 times higher increased risk of death observed for elective admissions on weekends than on weekdays (P for interaction = 0.001). Moreover, weekend admissions had significantly higher adjusted odds for cardiogenic shock, permanent pacemaker implantation, endocarditis, acute kidney injury, acute ischemic stroke, and blood transfusion. There was a trend of higher in-hospital mortality for weekend over weekday admissions throughout the study period. Conclusions Weekend admissions for TAVR had higher mortality, complications, and resource utilization, particularly in elective cases. Our findings suggest that patients admitted for TAVR during weekends are at high risk and warrant special attention.